Key to Parasitic Nematodes, Volume 1 Spirurata and Filariata - Skryabin, K.I., (Biology - Book Archive pre-2000., 1991)
This book is the first in a series which forms a part of the rich Soviet helminthological literature published in recent years. It deals with 197 species of nematodes belonging to suborders Spirurata and Filariata, re-examining and revising earlier descriptions and concepts related to them. A historical survey of the taxonomy of worms is given first, with keys to the various major groups and diagnoses of the nematode subclasses and orders. Even at this stage, certain new and interesting ideas are put forward. After a general account of the morphology and anatomy of each suborder, a diagnosis of each genius is given, together with an outline and drawing of its type species.